2019
DOI: 10.5114/ms.2019.86333
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of depression symptoms in adult high school students and the associated socio-demographic and environmental factors

Abstract: Introduction: Depression is a common mental health disorder and an important risk factor for somatic diseases. It affects various age groups, and early adulthood is associated with becoming independent and is a particularly critical period for developing depression. Aim of the research: A screening evaluation of depression symptom incidence in young adults in the context of the sociodemographic and school-, home-, and peer-related student situation. Material and methods: In 2018 a cross-sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The earliest stages of adulthood are associated with achieving maturity, making life choices, and becoming independent, all of which can be a serious psychological burden and pose a particular threat to mental health [6]. University students encounter significant levels of chronic stress over quite a long time, which can trigger the development of stressrelated health problems [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest stages of adulthood are associated with achieving maturity, making life choices, and becoming independent, all of which can be a serious psychological burden and pose a particular threat to mental health [6]. University students encounter significant levels of chronic stress over quite a long time, which can trigger the development of stressrelated health problems [7].…”
Section: Introductionmentioning
confidence: 99%
“…depression also has a significant impact on the impairment of professional performance [9]. Wiraszka et al [6] reported that, among the sociodemographic variables, the most influential factors affecting the severity of depressive symptoms in the studied group were gender and the economic status of the parents. Significantly more severe depressive symptoms were presented by girls and by students in a poor financial situation.…”
Section: Introductionmentioning
confidence: 99%